Strategi Adaptasi Komunikasi Orang Tua Generasi Z dalam Membina Hubungan dengan Anak melalui Media Sosial Instagram @talkparenting - Nurul Rahmadina; Anna Gustina Zainal; Ibrahim Besar; Nanda Utaridah; Nanang Trenggono (Lembaga Pengembangan Kinerja Dosen, 2025)
Digital media plays a crucial role as a primary source of information, reference, and inspiration in shaping parenting communication styles, particularly among younger parents such as Generation Z. Gen Z parents actively access social media content to gain insights into more empathetic and adaptive communication patterns for their children's needs. This study aims to understand how digital media consumption, particularly through the Instagram account @talkparenting, influences the parenting communication styles of Gen Z parents aged 23–28. This study employed a descriptive qualitative approach with data collection techniques through in-depth interviews and digital documentation of eight purposively selected informants. The results indicate that social media is not only a source of information but also functions as an agent of socialization of new values and norms in family communication practices. Gen Z parents tend to adopt an affective communication style—which emphasizes empathy, emotional validation, and acceptance—and an adaptive directive, a parenting approach that remains directive yet flexible and supportive of children's development. The educational content on the @talkparenting account serves as a primary reference in shaping their understanding of positive communication, conflict resolution, and emotional regulation in parent-child relationships. These findings support Kaplan and Haenlein's (2010) theory regarding the role of social media as an interactive platform that facilitates social learning and the transformation of interpersonal communication styles. This study highlights the importance of improving digital literacy among young parents, as well as the need to develop positive, educational, and relevant parenting content to support the formation of healthy communication patterns within the family. Thus, social media has great potential to become a strategic partner in supporting more conscious, reflective, and value-based parenting practices. Keywords: Communication Styles, Gen Z, Digital Media, Parenting, Communication Theory.